Проблема біженства у постбіполярну добу - Лабюк, Наталія Михайлівна (ЧНУ, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi.
Keywords: Міжнародні відносини, біженство